Design and characterization of a chloride-free organic copper solution: Electrochemical synthesis of Zn/Cu/Sn precursor stack for CZTS-based photoconversion devices. (10th March 2021) - Panzeri, G.; Dell'Oro, R.; Sansotera, M.; Marchionna, S.; Parravicini, J.; Acciarri, M.; Binetti, S.; Magagnin, L.
Highlights: Innovative procedure to electrodeposit copper onto zinc from an ethylene-glycol-based copper solution. Immersion potential measurements demonstrate a slower displacement reaction rate at increasing diethanolamine concentration. Diethanolamine (DEA) can form amine-complexes with copper in an ethylene-glycol-based solution. Mo(sub)/Zn/Cu/Sn stack can be obtained by plating copper on zinc. Abstract: In the present study, an ethylene glycol-based electrolyte is used to electrodeposit copper onto zinc for the synthesis of the Zn/Cu/Sn stack, precursor of Cu2 ZnSnS4 . The employed solution contains diethanolamine (DEA) which supports the formation of amine-complexes, whose features are studied by UV–vis absorption, ESI-MS, and FTIR measurements, providing insight on the optimal concentration of DEA for copper complexation. Cyclic voltammetries (CVs) are carried out at increasing [DEA]/[Cu 2+ ] ratios, highlighting the amine effect on the reduction potential of the copper species. The displacement reaction between copper and zinc is investigated by immersion potential measurements, showing a direct correlation to the voltammetric data. The optimized copper solution resulted in a negligible displacement contribution, allowing the electrochemical synthesis of Mo(sub) /Zn/Cu/Sn stack on a relatively large area (4 cm 2 ). The metallic precursor is analyzed by SEM/EDS, AFM, XRD, and GDOES techniques. Finally, the kesterite CZTS phase is obtained through reactive annealing with elemental sulfur and it is characterized by SEM/EDS, XRD, and Raman spectroscopy. Photoelectrochemical water splitting on CZTS/CdS/Pt heterostructure is carried out in an aqueous solution at pH 6.85, showing a photocurrent of -5.05 mA/cm 2 at 0 V vs RHE. A maximum applied bias photon-to-current efficiency (ABPE) value of 2.15% was found at 0.84 V bias. Graphical abstract: Image, graphical abstract